Innovative Cultivation Strategies for Echinochloa Colona in Marginal Lands as a Sustainable Livestock Feed Resource - Rezki Amalyadi (CV Media Inti Teknologi, 2025)
Background of Study: The growing global demand for high-quality livestock forage is increasingly constrained by land scarcity and climate variability. Marginal lands such as saline soils, degraded peatlands, and arid regions remain underutilized, yet hold promise for sustainable forage production without competing with prime agricultural land.Aims and Scope of Paper: this review aims to evaluate the potential of Echinochloa colona, a fast-growing and stress-tolerant wild grass, as a sustainable forage crop for cultivation on marginal lands, focusing on its agronomic performance, nutritional value, and contributions to livestock feed system sustainability.Methods: a narrative literature review was conducted using Scopus and Google Scholar, focusing on peer-reviewed articles published between 2004 and 2025, with 59 articles selected through a systematic screening process.Results: the findings show that E. colona thrives under adverse conditions, produces high biomass, and offers notable protein content, dietary fiber, and essential micronutrients that support livestock productivity. Agronomic enhancements such as minimum tillage, drip irrigation, biofertilizer use, and polyculture with legumes significantly improve its yield and quality. However, issues such as herbicide resistance, inadequate seed systems, limited farmer awareness, and lack of policy and market support remain barriers to adoption.Conclusion: integrating E. colona into marginal land-based livestock systems presents an opportunity to enhance feed security, combat land degradation, and foster climate-resilient agriculture through adaptive management, technological innovation, and supportive institutional frameworks.